2003
DOI: 10.1002/jcp.10312
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of functional voltage‐gated Na+ channel expression to cell behaviors involved in the metastatic cascade in rat prostate cancer: I. lateral motility

Abstract: Previous work suggested that functional voltage-gated Na(+) channels (VGSCs) are expressed specifically in strongly metastatic cells of rat and human prostate cancer (PCa), thereby raising the possibility that VGSC activity could be involved in cellular behavior(s) related to the metastatic cascade. In the present study, the possible role of VGSCs in the lateral motility of rat PCa cells was investigated in vitro by testing the effect of modulators that either block or enhance VGSC activity. Two rat PCa cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
134
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(146 citation statements)
references
References 45 publications
7
134
2
Order By: Relevance
“…29,[31][32][33] In this study, we observed Brn3a[s]-specific transcriptional regulation of SCN9A/Nav1.7 in PC-3 cells with both stable and transient overexpression of this transcription factor. This is the first example of gene regulation by the short isoform of a Brn-3 protein only.…”
Section: Upregulation Of Brn-3a[s] In Cap and Role In Growthmentioning
confidence: 65%
See 1 more Smart Citation
“…29,[31][32][33] In this study, we observed Brn3a[s]-specific transcriptional regulation of SCN9A/Nav1.7 in PC-3 cells with both stable and transient overexpression of this transcription factor. This is the first example of gene regulation by the short isoform of a Brn-3 protein only.…”
Section: Upregulation Of Brn-3a[s] In Cap and Role In Growthmentioning
confidence: 65%
“…The Nav1.7 VGSC has been shown to potentiate cellular processes integral to CaP metastasis in vitro, especially invasion 27,[31][32][33] and VGSCs have been found to increase the invasiveness of lymphocytes and breast cancer cells. 49,51 Brn-3 proteins have also recently been found to have a role in cellular invasion, with overexpression of Brn-3b significantly potentiating neuroblastoma cell invasion through Matrigel.…”
Section: Upregulation Of Brn-3a[s] In Cap and Role In Growthmentioning
confidence: 99%
“…A similar mechanism of action of sodium channel blockade also may be relevant in tumor cell biology. In neoplastic cells that express intracellular sodium channels, particularly NaV1.6-positive melanomas, functional block of sodium channels might prevent metastasis through both a direct interaction with the tumor cell as well as effects on macrophages and endothelial cells (9,34,35). Additional studies are required to assess the therapeutic potential of sodium channel blockers in these disease states.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike NaV1.5, NaV1.6 is also expressed in unprimed human macrophages and in unprimed and primed mouse macrophages and microglia (7,8). Many invasive neoplastic cell lines also express voltage-gated sodium channels, which may regulate their ability to metastasize (9).…”
mentioning
confidence: 99%
“…MTT assay A total of 2 Â 10 3 cells per well were plated in 96-well plates with 200 ml media per well as control (Fraser et al, 2003). Cells were washed with serum-free media, and incubated with serum-free media with or without 100 ng/ml of NGF and dimethyl sulfoxide (DMSO) or 1 mM AG1478, AG825 or AG1295 for 48 h at 32 or 37 1C.…”
Section: Chip Assaysmentioning
confidence: 99%